1996
DOI: 10.1136/hrt.76.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Specific changes in skeletal muscle myosin heavy chain composition in cardiac failure: differences compared with disuse atrophy as assessed on microbiopsies by high resolution electrophoresis.

Abstract: Objective-In congestive heart failure (CHF) the skeletal muscle of the lower limbs develops a myopathy with atrophy and shift from the slow type to the fast type fibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 30 publications
5
75
0
3
Order By: Relevance
“…Although many functional differences between fiber types have been ascribed to myosin composition (1,15), variation in the composition of thin-filament proteins, such as troponin C, I, and T isoforms (20,22,23), could also contribute. This point is particularly relevant to our results since our laboratory (31) and others (36) have shown alterations in fiber-type distribution in CHF, with a shift toward a more fast-twitch phenotype. To directly test whether variation in fiber type affects thinfilament function, we isolated native thin filaments from rat EDL and soleus muscles [composed primarily of fast-twitch and slow-twitch fibers, respectively (32)] and characterized their function using the in vitro motility assay.…”
Section: Discussionmentioning
confidence: 65%
“…Although many functional differences between fiber types have been ascribed to myosin composition (1,15), variation in the composition of thin-filament proteins, such as troponin C, I, and T isoforms (20,22,23), could also contribute. This point is particularly relevant to our results since our laboratory (31) and others (36) have shown alterations in fiber-type distribution in CHF, with a shift toward a more fast-twitch phenotype. To directly test whether variation in fiber type affects thinfilament function, we isolated native thin filaments from rat EDL and soleus muscles [composed primarily of fast-twitch and slow-twitch fibers, respectively (32)] and characterized their function using the in vitro motility assay.…”
Section: Discussionmentioning
confidence: 65%
“…Both approaches have the advantage of providing abundant muscle tissue for reliable biochemical, histochemical and histomorphometric analyses [24], but their major drawback is limited patient acceptance and the difficulty of obtaining serial biopsies in a given subject. Using a 17-gauge needle and a different automated device than that of the current authors, VESCOVO et al [13,14] showed that it is possible to determine the MyoHC composition of the gastrocnemius muscle in patients with chronic heart failure with the microbiopsy procedure. However, their specimen weighed only 50-200 mg, which is too little for enzymatic activity or histological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Their relative invasiveness makes it difficult to obtain several biopsies from the same subjects to study, due to, for instance, the time-course response of the skeletal muscle to interventions, such as exercise training or anabolic drug supplementation [9]. Less invasive alternatives to the semiopen muscle biopsy have been proposed by several authors working in different medical areas, such as muscular oncology [10], neuromuscular diseases [11,12] and cardiac failure [13,14]. Fine-needle muscle biopsies, also termed microbiopsies, were successfully used to obtain muscle tissue in several studies, but, to the current authors' knowledge, the results obtained with these techniques have never been compared with the semi-open techniques.…”
mentioning
confidence: 99%
“…Recent studies reported that chronic inadequate blood flow in the diaphragmatic muscle (the main respiratory muscle) in CHF patients results in muscular degeneration and increased fragility of the diaphragm, which is the cause of diaphragmatic muscle fatigue at a low minute ventilation volume, and early recruitment of the accessory respiratory muscles. [17][18][19][20] Therefore, respiratory muscle fatigue in CHF patients is not only associated with high frequency fatigue but also with low frequency fatigue caused by muscular tissue damage.…”
Section: Discussionmentioning
confidence: 99%